1997
DOI: 10.4049/jimmunol.158.3.1458
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of an altered redox state in hyporesponsiveness of synovial T cells in rheumatoid arthritis.

Abstract: In rheumatoid arthritis (RA), T cells isolated from the synovial fluid (SF) show impaired responses to mitogenic stimulation compared with T cells from the peripheral blood (PB). Here it is reported that hyporesponsiveness of SF T cells correlated with a significant decrease in the levels of the intracellular redox-regulating agent glutathione (GSH). GSH was decreased in both CD4+ (p = 0.0022) and CD8+ (p = 0.0010) SF T cell subsets compared with PB CD4+ and CD8+ T cells in RA patients. Levels of thioredoxin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…27 Further, the synovial fluid of rheumatoid arthritis patients has been shown to be highly oxidizing relative to that of a non-arthritic control group. 43,44 A significant body of literature suggests that when overexpressed at sites of inflammation, 16 MIF can endure large swings in environmental redox potential, consistent with our determination of the MIF redox potential in vitro using solution NMR 45,46 (Figure S12, midpoint 𝐸 " # = -215 ± 5 mV, near normal physiological range). NMR spin relaxation studies show redox-dependent modulation of local flexibility in MIF, with motion observed on multiple timescales.…”
Section: Discussionsupporting
confidence: 84%
“…27 Further, the synovial fluid of rheumatoid arthritis patients has been shown to be highly oxidizing relative to that of a non-arthritic control group. 43,44 A significant body of literature suggests that when overexpressed at sites of inflammation, 16 MIF can endure large swings in environmental redox potential, consistent with our determination of the MIF redox potential in vitro using solution NMR 45,46 (Figure S12, midpoint 𝐸 " # = -215 ± 5 mV, near normal physiological range). NMR spin relaxation studies show redox-dependent modulation of local flexibility in MIF, with motion observed on multiple timescales.…”
Section: Discussionsupporting
confidence: 84%
“…The first study published in this field was on the effect of redox status on rheumatoid arthritis published in 1997 [ 29 ]. This study found that altered redox status had an important role in the hyporesponsiveness of joint T cells in patients with rheumatoid arthritis, revealing part of the mechanism by which oxidative stress causes rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…However, under specific pathological conditions like autoimmunity, allergy, chronic inflammation, COVID-19, and acute GvHD, there is a need to suppress T-cell activation (Maurice et al . 1997 ; Griffiths et al . 2011 ; Weyand et al .…”
Section: Discussionmentioning
confidence: 99%